2013
DOI: 10.1149/05201.0489ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Surface Adsorption of CMP Slurry Additives on Abrasive Particles

Abstract: Fluorescence correlation spectroscopy (FCS) is used to study additive-abrasive particle interactions in chemical-mechanical planarization (CMP) slurries. FCS provides quantitative determinations of the binding between additives and abrasive particles by characterizing the competitive adsorption of the additive and a fluorescent probe molecule, Alexa fluor 546 (A546) at the surface of a silica abrasive particle. Analysis of the adsorption of benzotriazole (BTA) on colloidal silica confirms the displacement of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…20 In the present study, the analytical capabilities of one particular single-molecule spectroscopic technique, fluorescence correlation spectroscopy (FCS), 18 are highlighted for colloidal silica dispersions used in CMP processes. This work expands on previously reported preliminary FCS findings for this class of slurries [21][22][23] and identifies future areas of application of the technique for CMP slurry characterization.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…20 In the present study, the analytical capabilities of one particular single-molecule spectroscopic technique, fluorescence correlation spectroscopy (FCS), 18 are highlighted for colloidal silica dispersions used in CMP processes. This work expands on previously reported preliminary FCS findings for this class of slurries [21][22][23] and identifies future areas of application of the technique for CMP slurry characterization.…”
supporting
confidence: 78%
“…Preliminary FCS studies have demonstrated that the copper CMP additives BTA and glycine interact with the surface of a precipitated silica abrasive (d H = 115 ± 1 nm). [21][22][23] As shown in Figure 6, the degree of A546 adsorption was reduced by BTA in silica-dye mixtures. Separate FCS studies confirmed that de-sorption of A546 was not due to a more favorable binding interaction between A546 and BTA in solution.…”
Section: Resultsmentioning
confidence: 81%
“…Recent FCS studies have reported the analysis of adsorption of chemical compounds in model CMP slurries to silica abrasive particles in the slurries (6,7). In the present study, the application of FCS for the quantitative determination of particle size distribution of colloidal silica abrasive dispersions is described.…”
Section: Introductionmentioning
confidence: 99%
“…These hydroxyl groups form hydrogen bonds with the silica abrasive and absorb the silica abrasive strongly onto the surface. 26 In addition to particle residues, the complexing agents in Co cleaning affected the formation of recesses in the Co contact. Figure 4 shows the top and cross-sectional TEM images of the patterned Co contacts after CMP and cleaning.…”
Section: Resultsmentioning
confidence: 99%